PENGARUH EFIKASI DIRI DAN PERSEPSI IKLIM ORGANISASI TERHADAP KINERJA DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL MEDIATOR PADA KARYAWAN BMT BIF YOGYAKARTA - Fajriah, Nailul; Darokah, Marcham (Universitas Ahmad Dahlan, 2016)
AbstractThe purpose of this study is to examine what are the most affect factors to BMT BIF employee performance, in terms of self-efficacy and perceptions of organizational climate, moderated by employee engagement. This study uses a quantitative approach in an effort to test the hypotheses. The subjects were all employees of microfinance bank (BMT) BIF Yogyakarta totaling 93 people. Methods of data collection using a Likert scale with five answer options. Data were analyzed using Structural Equation Modeling (SEM) was run by AMOS 22.0 software. The results showed 19.4% of BMT BIF employee’s performanceis influenced by self-efficacy, the parameter coefficient of 0.440 and P value <0.05. Selfefficacy significantly affect to employee performance of which is mediated by employee engagement. These results demonstrate the effective contribution of 17.6% with a coefficient parameter of 0.420 and P value <0.05. Perceive of organizational climate does not affect to BMT BIF employee performance, either directly or mediated by employee engagement.Keywords: employee engagement, job performance. Perceived of organizational climate,self-efficacy